Internationally recognised index macro- and microfossils used to define the Upper Cretaceous stages boundary - Jaff, Rawand Bakir Noori (Sulaimani Journal for Pure and Applied Sciences, 2017)
The Cretaceous system (145-66 Ma) in the history of the Earth can be divided into two series, which are the Lower Cretaceous and the Upper Cretaceous. The Upper Cretaceous can be divided into six stages (Cenomanian, Turonian, Coniacian, Santonian, Campanian and Maastrichtian). The boundaries between some of the Upper Cretaceous stages are now well defined in different localities in the world especially in Europe. The Upper Cretaceous stages boundaries were primarily defined by ammonites, inoceramid bivalves, belemnites, crinoids and in some cases planktonic foraminifera as well. At the moment four out of the six Upper Cretaceous stages boundaries are now formally ratified as the Global Boundary Stratotype Section and Point (GSSP). The formally ratified GSSP boundaries which are approved by the International Union of Geological Sciences are (Cenomanian, Turonian, Santonian and Maastrichtian). Due to relatively rare of ammonoid groups in the Cenomanian, therefore, the base of the Cenomanian Stage can be defined by the lowest occurrence of the planktonic foraminifera Thalmanninella globotruncanoides. After considering several potential placements, the Turonian Working Group placed the base of the ammonite Watinoceras devonense for the base of the Turonian Stage. The sudden turnover from Magadiceramus inoceramid bivalves to the lowest occurrence of the widespread inoceramid Platyceramus undulatoplicatus has been selected as the marker for the base of the Santonian. The Maastrichtian Working Group recommended the base of the Maastrichtian to be assigned as the lowest occurrence of ammonoid Pachydiscus neubergicus that has a much wider geographic distribution than belemnite Belemnella lanceolata.
Keywords: Upper Cretaceous; Thalmanninella globotruncanoides; Watinoceras devonense; Platyceramus undulatoplicatus; Pachydiscus neubergicus